Epigenetic Modifications in Placenta are Associated with the Child's Sensitization to Allergens. (17th April 2019) - Harb, Hani; Alashkar Alhamwe, Bilal; Acevedo, Nathalie; Frumento, Paolo; Johansson, Catharina; Eick, Lisa; Papadogiannakis, Nikos; Alm, Johan; Renz, Harald; Potaczek, Daniel P.; Scheynius, Annika
Abstract : Prenatal environmental exposures are considered to contribute to the development of allergic sensitization by epigenetic mechanisms. The role of histone acetylation in the placenta has not been examined yet. We hypothesized that placental histone acetylation at the promoter regions of allergy-related immune regulatory genes is associated with the development of sensitization to allergens in the child. Histones H3 and H4 acetylation at the promoter regions of 6 selected allergy-related immune regulatory genes was assessed by a chromatin immunoprecipitation assay in 173 term placentas collected in the prospective birth-cohort ALADDIN. The development of IgE sensitization to allergens in the children was followed from 6 months up to 5 years of age. We discovered significant associations of histone acetylation levels with decreased risk of allergic sensitization in 3 genes . Decreased risk of sensitization to food allergens was associated with higher H3 acetylation levels in placentas at the IFNG and SH2B3 genes, and for H4 acetylation in HDAC4 . Higher HDAC4 H4 acetylation levels were also associated with a decreased risk of sensitization to aeroallergens. In conclusion, our results suggest that acetylation of histones in placenta has a potential to predict the development of sensitization to allergens in children.